Experiences of Emirati families in dealing with their addicted children: A field study on a sample of families of addicts at the Irada Center for Addiction Treatment and Rehabilitation in the Emirate of Dubai - Alali, Khadija; Yaiche, Ouassila (Al-Adab Journal, 2025)
The study aimed to explore the experiences of Emirati families in dealing with their children who are addicted to drugs, and to determine their level of awareness of methods of proper dealing with these children. The study also sought to evaluate the extent to which families accept their addicted children and identify the challenges they face in providing support, in addition to reviewing the role of treatment centers in supporting these families. The study relied on a case study approach using semi-directed interviews with an intentional sample of 16 family members of addicts receiving treatment at the Irada Treatment and Rehabilitation Center in the Emirate of Dubai. The results revealed the need for families to have more awareness and education about how to deal with addicted children, whether before or after starting treatment, as it was found that families suffer from a weakness in accepting their addicted children, especially in the early stages of discovering addiction. Families also faced several challenges, most notably: cutting expenses, forcing children to stay away from bad friends, providing emotional and psychological support, and social stigma associated with addiction. In addition, the study showed the effectiveness of the treatment and rehabilitation programs provided by the Irada Center, which won the approval of families in terms of the quality of care and programs provided. The study recommended intensifying awareness campaigns about the dangers of addiction, targeting families and students in schools and universities, and directing them on how to detect and deal with addiction. She also stressed the need to involve parents in all stages of children’s treatment, and to provide them with the necessary support during the rehabilitation period.